2024
DOI: 10.1093/jas/skae067
|View full text |Cite
|
Sign up to set email alerts
|

Processing of corn-based dog foods through pelleting, baking and extrusion and their effect on apparent total tract digestibility and colonic health of adult dogs

Isabella Corsato Alvarenga,
Ryan Lierz,
Youhan Chen
et al.

Abstract: Different food processing parameters may alter starch granule structure and its cooking degree. With lower thermomechanical energy, more resistant starch (RS) is retained in the food, which may benefit gastrointestinal (GI) health. The objective of this study was to determine the effect of food processing on dietary utilization and dog gut health. Experimental diets containing 56% corn as the sole starch source were produced through pelleting, baking, and extrusion and compared to a baked control diet in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Studies in both humans and animals have found that carbohydrate fermentation by the GI microbiome leads to the increased production of metabolites such as saccharolytic short-chain fatty acids (SCFAs), which have been shown to provide anti-inflammatory and immunomodulatory activity, among other effects (19)(20)(21). Common dog food processing methods such as baking and extrusion have been shown to support increased SCFA production when compared to a minimally-processed control (22).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in both humans and animals have found that carbohydrate fermentation by the GI microbiome leads to the increased production of metabolites such as saccharolytic short-chain fatty acids (SCFAs), which have been shown to provide anti-inflammatory and immunomodulatory activity, among other effects (19)(20)(21). Common dog food processing methods such as baking and extrusion have been shown to support increased SCFA production when compared to a minimally-processed control (22).…”
Section: Introductionmentioning
confidence: 99%
“…Along with the 32,000-year history of the parallel evolution between dogs and humans and adapting to agricultural-based living conditions, dogs evolved from carnivores to omnivores due to large changes in their food source [ 7 ]. Both animal ingredients and plant ingredients containing large amounts of protein and starch can be digested and absorbed by dogs [ 8 , 9 ]. To save animal protein-sourced protein and protect the environment, it would be a better way to use more plant-sourced protein and recycled protein to replace part of animal-sourced protein in pet food.…”
Section: Introductionmentioning
confidence: 99%